2021
DOI: 10.1155/2021/9971425
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Consumer Intentions for Foods with Antioxidant Properties: Predictors of Choice and Purchase Barriers

Abstract: Today, food products not only should serve the source of main nourishment but also must minimize the risk of negative impact on the human body. Products enriched with antioxidants can be referred to such category. For food producers, the development of products “for health” is usually connected with significant investment, whereas the final success of innovative products does not always meet the expectations. The greatest part of such products is withdrawn from the market during the first year. It is important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Therefore, given the sensory acceptance of beverages with microencapsulated extracts, as well as the high antioxidant activity, quantity and bioaccessibility of phenolic compounds and stability of these compounds observed in this study, these extracts can form an aid strategy against non-communicable and chronic diseases, mainly insulin resistance, cardiovascular diseases, cancer, etc., due to the ability to scavenge free radicals, preventing them from acting negatively on metabolic pathways and DNA damage [ 40 , 41 ]. Thus, given the growing interest of the population in products with health benefits, including antioxidant foods [ 42 ], these developed extracts can add value to the food products and health to the population.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, given the sensory acceptance of beverages with microencapsulated extracts, as well as the high antioxidant activity, quantity and bioaccessibility of phenolic compounds and stability of these compounds observed in this study, these extracts can form an aid strategy against non-communicable and chronic diseases, mainly insulin resistance, cardiovascular diseases, cancer, etc., due to the ability to scavenge free radicals, preventing them from acting negatively on metabolic pathways and DNA damage [ 40 , 41 ]. Thus, given the growing interest of the population in products with health benefits, including antioxidant foods [ 42 ], these developed extracts can add value to the food products and health to the population.…”
Section: Resultsmentioning
confidence: 99%
“…The information included in the label of foods, such as the reported health claims and nutritional value, were therefore positively affecting consumer purchasing choices [69] and should provide consumers with the adequate information on the beneficial role of food products, always in accordance with EU Commission principles [70] to avoid misleading them [71]. However, it should be noted that consumers are not always familiar with the terms used to describe the nutritional value of products, and therefore it remains important to promote an understanding of the beneficial role of nutrients [68], such as in the case of antioxidant and phenolic compounds [72]. In addition, it is reported that consumers are not aware of the specific nutrient food sources for antioxidants and phenolics [73,74], and this can be evaluated as a barrier affecting their food purchasing behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to several factors. Firstly, some studies have shown that there is a misunderstanding among consumers regarding the role of antioxidants in the human body, leading to a perception of risk associated with such purchases (Fatkullin et al, 2021). Secondly, while consumers generally view the use of natural antioxidants favorably (Mitterer-Daltoé et al, 2020;Lungu et al, 2020), industrial food processing relies on a wide range of technical and chemically synthesized additives that can be used as antioxidants for food preservation.…”
Section: Demand Estimationmentioning
confidence: 99%